(untitled) (Sustainability in Debate, 2021)
The saturation of hinterland accentuates adverse environmental impacts and socio-spatial conflicts, demanding logistical alternatives. As a solution, the dry port enables the decentralization of customs, handling, and storage operations, which mitigates part of the problems, in addition to stimulating the economy in the region where it operates. Thus, its location is crucial for the efficiency of import and export logistic systems. This paper aimed to evaluate the spatial distribution of dry ports in Minas Gerais, Brazil, and to identify the best locations for a new installation. The methodology put together two recognized methods for location definition: the Spatial Multicriteria Analysis and the Location-Allocation Problem. The first, in line with the most current practices in transportation planning, integrated social, environmental and technical criteria. The second adopted the first’s result as weighted demand and applied a metaheuristic to solve an optimization problem. Findings show the regional disparity and the deficiency of logistic infrastructures in the north of Minas Gerais. All scenarios point to the Montes Claros region as a candidate for the installation of a dry port. The possibility of reconciling society, environment and economy in infrastructure planning was demonstrated. Â